Italy-Assessing Competition and Efficiency in the Banking System. (IMF Working Papers; Working Paper ;, 2007)
The paper assesses the degree of banking competition and efficiency in Italy?over time as well as compared to that in other countries, such as France, Germany, Spain, the United Kingdom, and the United States. The paper finds competition in the Italian banking sector has intensified in loan and deposit markets in recent years, but banks still operate in a highcost, high-income system, particularly with respect to retail/services, and efficiency gains have yet to fully materialize. The degree of competition falls within the range of estimates for a set of comparator countries. Greater contestability should act as a powerful force to drive banks to become more competitive and efficient. Competition policy will also continue to be an important consideration, both in enforcing Italy's antitrust laws and in ensuring that the procedures for dealing with weak banks and other merger and acquisition reviews focus on stability and competition objectives.